Silencing Gene‐Engineered Injectable Hydrogel Microsphere for Regulation of Extracellular Matrix Metabolism Balance (Small Methods 4/2022). Issue 4 (18th April 2022) - Chang, Hongze; Cai, Feng; Zhang, Yan; Jiang, Mingwei; Yang, Xiaolong; Qi, Jin; Wang, Lei; Deng, Lianfu; Cui, Wenguo; Liu, Xiaodong
Abstract : Rechargeable Batteries In article number 2101201, Wenguo Cui, Xiaodong Liu, and co‐workers construct an injectable circRNA silencing‐hydrogel microsphere, capable of targeting nutrient‐restricted microenvironments to regulate the extracellular matrix metabolism balance by grafting circSTC2 silencing genes‐loaded DOTAP/Chol/DOPE cationic liposomes on methacrylated hyaluronic acid microspheres via amide bonds, which can precisely control the release of gene vectors and effectively silence pathological genes in nucleus pulposus cells.